Smoke Composition of Burning Fire in Dry Deciduous Dipterocarp Forest at Huai Kha Khaeng Wildlife Sanctuary, Uthai Thani Province - Himmapan, Woraphun; Kaitpraneet, San (วารสารวนศาสตร์ไทย, 2022)
Smoke composition of burning fire in dry deciduous dipterocarp forest at Huai Kha Khaeng Wildlife Sanctuary was studied in twelve 30 x 30 m2 plots with completely randomized design. Smoke composition was investigated in three plots per each month from January to April in 2003 and 2004. The smoke composition was recorded every two minutes in eight cardinal directions during burning. Comparisons of the result differences between the first year and second year were made. The results revealed that the surface fire intensity was not severe. Smoke composition included CO, NO2, SO2 and CO2. Concentrations of them from the first year burning were 48.87 ppm, 1.86 ppm, 0.46 ppm and 0.12 percent, respectively. Almost all gas concentrations from the first year burning were generally higher than those of the 1995 one hour Ambient Air Standards of Thailand. Those from the second year burning were not significantly different from the first year burning (CO = 28.27 ppm, NO2=1.61 ppm, SO2 = 0.21 ppm and CO2 = 0.08 percent), and these gas concentrations were near the 1995 one hour Ambient Air Standards of Thailand. Almost all of the gas concentrations in the smoke composition from burning were higher than those of the 1995 one hour Ambient Air Standards of Thailand. Key words: smoke composition, burning fire, dry deciduous dipterocarp forest, Huai Kha Khaeng Wildlife Sanctuary